Rural school Students’ Attitudes Toward EFL Learning( A Survey Study At Seventh Grade Students of SMPN 28 Seluma - Akbarjono, Ali; Martina, Feny; Hariswa, Nanda Nur Asa (Yayasan Darussalam Bengkulu, 2022)
The main purpose of this research is to discover and describe seventh-grade students' attitudes toward EFL learning at SMPN 28 Seluma. When a student participates in class, he exhibits certain behaviors. The descriptive-quantitative method was used in this study. This study's population consisted of 41 students in seventh grade. A quota sampling technique was used to collect samples from 41 students. A questionnaire about student responses was used to collect data in this study. A positive questionnaire with 15 items and a negative questionnaire with 15 items comprise the questionnaire. The results of data analysis based on the questionnaire showed an average value of 73.215, meaning that students had a positive attitude towards EFL learning.